2014
DOI: 10.2478/s13382-014-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of exposure to electromagnetic radiofrequency radiation in the indoor workplace accessible to the public by the use of frequency-selective exposimeters

Abstract: Investigations confirmed the practical applicability of the exposimetric measurements technique for evaluating parameters of worker's exposure in both frequency- and time-domain. The presented results show EMRR exposure of workers or general public in locations comparable to offices to be well below international limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
4
11
0
4
Order By: Relevance
“…The level of exposure to RF-EMR is significantly lower than the general public exposure limit provided by international guidelines and legislation established in various countries (4-61 V/m) (Council Recommendation, 1999; Gryz et al, 2014a;Stam, 2011;ICNIRP, 1998). system switched-on, talk between engine-driver and traffic operator sensitivity of meter Although the total level of RF-EMR exposure in metro is comparable with typical scenarios existing in urban areas, the specific conditions of EMF radiation propagation inside the underground infrastructure (such as the underground location of tubes and stations -closed spaces rounded by walls), mean that specific character of this exposure needs attention when health hazards from exposure are discussed -in the context of frequency composition, spatial distribution and the ratio between electric and magnetic components (i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The level of exposure to RF-EMR is significantly lower than the general public exposure limit provided by international guidelines and legislation established in various countries (4-61 V/m) (Council Recommendation, 1999; Gryz et al, 2014a;Stam, 2011;ICNIRP, 1998). system switched-on, talk between engine-driver and traffic operator sensitivity of meter Although the total level of RF-EMR exposure in metro is comparable with typical scenarios existing in urban areas, the specific conditions of EMF radiation propagation inside the underground infrastructure (such as the underground location of tubes and stations -closed spaces rounded by walls), mean that specific character of this exposure needs attention when health hazards from exposure are discussed -in the context of frequency composition, spatial distribution and the ratio between electric and magnetic components (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Investigations involving this new technique of using exposimeters for assessing RF-EMR in various environments have been on-going in Poland since 2011, and have included a systematic study on the metrological properties of frequencyselective exposimeters, the relationship between the results of exposimetric investigations and unperturbed RF-EMR in the case of various ways of using exposimeters and exposure analysis in various environments (Gryz et al, 2012(Gryz et al, , 2014a(Gryz et al, ,b, 2015. Based on preliminary studies, RF-EMR exposure inside the underground metro infrastructure has been identified as an example of an environment where some specific parameters of exposure profile are expected.…”
Section: Introductionmentioning
confidence: 98%
“…Z punktu widzenia bezpieczeństwa pracy istotne jest wskazanie urządzeń emitujących pole elektromagnetyczne o ekstremalnie niskiej częstotliwości (extremely low frequency -ELF) i o częstotliwości radiowej (radio frequency -RF). Urządzenia elektroenergetyczne to źródła pola o niskiej częstotliwości, a urządzenia telekomunikacyjne są źródłami pola o wysokiej częstotliwości [9,10]. Dopuszczalny poziom emisji pola EMF podlega ścisłym regulacjom prawnym, których celem jest zapewnienie bezpieczeństwa pracowników w miejscu pracy.…”
Section: Szkodliwe Działanie Pola Emfunclassified
“…The biological consequences derive from the radiation conditions, such as the strength of the dose, way of fractioning, mass and type of tissues exposed to radiation, as well as their oxygenation. The effects of the exposure to radioactivity depends also on the individual biological characteristics of a body [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%